2021
DOI: 10.11152/mu-2730
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of contrast-enhanced ultrasound for detecting the staging and grading of bladder cancer: a systematic review and meta-analysis

Abstract: Aim: The study retrospectively analysed the accuracy of preoperative contrast-enhanced ultrasound (CEUS) in differenti-ating stage Ta-T1 or low-grade bladder cancer (BC) from stage T2 or high-grade bladder cancer. Material and methods: We systematically searched the literature indexed in PubMed, Embase, and the Cochrane Library for original diagnostic articles of bladder cancer. The diagnostic accuracy of CEUS was compared with cystoscopy and/or transurethral resection of bladder tumors (TURBT). The bivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Mehmet Sami et al [ 30 ] use SWE to evaluate the fibrosis of CKD in a study, and the results shows a highly correlation with the elasticity measurement of fibrosis patients in renal biopsy (P = 0.046). Likelihood ratio (LR) is a comprehensive indicator that reflects the diagnostic value of diagnostic experiments [ 31 , 32 ]. In our study, PLR-P is 4.29 (95% CI: 3.43 - 5.37) and PLR-N is 0.20 (95% CI: 0.16 - 0.25), providing “strong” diagnostic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Mehmet Sami et al [ 30 ] use SWE to evaluate the fibrosis of CKD in a study, and the results shows a highly correlation with the elasticity measurement of fibrosis patients in renal biopsy (P = 0.046). Likelihood ratio (LR) is a comprehensive indicator that reflects the diagnostic value of diagnostic experiments [ 31 , 32 ]. In our study, PLR-P is 4.29 (95% CI: 3.43 - 5.37) and PLR-N is 0.20 (95% CI: 0.16 - 0.25), providing “strong” diagnostic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…This staging is not related only to the clinical management of the patient, especially to the surgical approach, but also closely related to prognosis [17]. CEUS can achieve comparable sensitivity and specificity to MRI in staging of BC, which suggests that CEUS is a valuable method in preoperative staging of BC [18]. VI-RADS was originally developed to standardize MRI image collection in BC patients at risk for muscularis invasion [9], but our results showed that the VI-RADS scoring system based on US and CEUS can be used for the same purpose.…”
Section: Discussionmentioning
confidence: 99%
“…The limit of the CT study of the lymph nodes is the potential over-staging, detected in about 30% of cases with reactive lymphadenopathies with a short axis greater than 10 mm. Sub-staging is possible in case of lymph nodes with dimensions within the limits, but nevertheless the site of micro-metastases [25].…”
Section: Ct-urographymentioning
confidence: 99%